2011
DOI: 10.1017/s1355617710001566
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological Clustering Highlights Cognitive Differences In Young People Presenting With Depressive Symptoms

Abstract: Early stages of affective or psychotic disorders may be accompanied by neuropsychological changes that help to predict risk of developing more severe disorders. A comprehensive set of neuropsychological measures was collected in 109 help-seeking young people (16 to 30 years; 54 females), recently diagnosed with an affective or psychotic disorder and presenting with current depression. Hierarchical cluster analysis determined three clusters: one deemed to have a "poor memory" profile (n = 40); another with a "p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
78
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(85 citation statements)
references
References 59 publications
7
78
0
Order By: Relevance
“…The presence of patients with mood disorders in all three clusters suggests that individual characteristics may play a more prominent role in cognitive functioning than diagnostic category. This conclusion supports the findings of previous cluster studies, which identify variable levels of cognitive impairment in samples with BD and MDD (Burdick et al, 2014;Hermens et al, 2011). The distribution of clusters identified in the present study was also similar to that revealed by other similar investigations of psychiatric samples.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The presence of patients with mood disorders in all three clusters suggests that individual characteristics may play a more prominent role in cognitive functioning than diagnostic category. This conclusion supports the findings of previous cluster studies, which identify variable levels of cognitive impairment in samples with BD and MDD (Burdick et al, 2014;Hermens et al, 2011). The distribution of clusters identified in the present study was also similar to that revealed by other similar investigations of psychiatric samples.…”
Section: Discussionsupporting
confidence: 93%
“…The hierarchical clustering procedure used in this study was similar to that described in previous investigations of similar populations (Burdick et al, 2014;Hermens et al, 2011). Patterns of neuropsychological performance were identified using Ward's method of minimum variance (Ward, 1963) with a 586 C. Cotrena et al…”
Section: Discussionmentioning
confidence: 99%
“…Our group has previously shown similar cognitive heterogeneity in a sample of younger depressed subjects diagnosed with anxiety disorder, depressive disorder, bipolar disorder or first-episode psychosis (Hermens et al 2011). As shown in the study by Burdick et al (2014), our cluster analysis also revealed three distinct neuropsychological subgroups.…”
supporting
confidence: 80%
“…Participants were recruited as part of a wider Youth Mental Health cohort study (Hermens et al, 2011, Lee et al, 2013, with referral from psychiatrists with a diagnosed bipolar illness using DSM-IV criteria (APA, 2000) as follows: bipolar I (n = 19), bipolar II (n = 30) or bipolar spectrum with family history of BD (n =21) or bipolar NOS (n = 7), defined as an illness pattern consisting of periods of both elevated and depressed mood consistent with a bipolar spectrum disorder (Angst, 2007). Participants were asked at baseline whether they would be interested in being contacted for a follow-up assessment.…”
Section: Participantsmentioning
confidence: 99%